Peran Orang Tua dalam Perawatan Kesehatan Gigi pada Anak Down Syndrome Usia 4 - 6 Tahun - Isnaini fatwa yanti; Reni Pawestuti Ambari Sumanto (Jurnal Kesehatan Gigi dan Mulut (JKGM), 2026)
Background: Children with Down Syndrome have limitations in motor and cognitive abilities, requiring parental involvement in dental health care. Objective: This study aims to determine the role of parents in dental health care for children with Down Syndrome aged 4–6 years. Methods: This study used a qualitative method with a case study approach to explore the role of parents in dental health care for children with Down Syndrome aged 4–6 years. Data collection was conducted through interviews and observations. Results: The results of this study indicate that dental health care for children aged 4–6 years is significantly influenced by the role of parents, parenting styles, family functions, and the Health Belief Model. Conclusion: The conclusion of this study is that dental health care for children with Down Syndrome is inseparable from the role of parents, parenting styles such as democratic and permissive, family functions such as religious, sociocultural, love, socialization, and education, and the Health Belief Model, including perceived susceptibility and perceived barriers.